Biochemical characterization of an acetylesterase from Bacillus subtilis and its application for 7-aminocephalosporanic acid deacetylation - Wang, Xiaoliang; Nong, Sujin; Li, Jiayi; Liu, Yan; Wu, Qian; Huang, Zunxi; Xu, Bo; Ding, Junmei (Frontiers in Microbiology, 2023)
Deacetyl-7-aminocephalosporanic acid (D-7-ACA), which could be converted from 7-aminocephalosporanic acid (7-ACA), is a crucial starting material that is used for synthesizing industrial semisynthetic β-lactam antibiotics. Enzymes involved in the conversion from 7-ACA to D-7-ACA present critical resources in the pharmaceutical industry. In the present study, a putative acetylesterase, EstSJ, identified from Bacillus subtilis KATMIRA1933, was first heterologously expressed in Escherichia coli BL21(DE3) cells and biochemically characterized. EstSJ belongs to carbohydrate esterase family 12 and is active on short-chain acyl esters from p-NPC2 to p-NPC6. Multiple sequence alignments showed that EstSJ was also an SGNH family esterase with a typical GDS(X) motif at its N-terminal end and a catalytic triad composed of Ser186-Asp354-His357. The purified EstSJ displayed the highest specific activity of 1,783.52 U mg–1 at 30°C and pH 8.0, and was stable within the pH range of 5.0–11.0. EstSJ can deacetylate the C3′ acetyl group of 7-ACA to generate D-7-ACA, and the deacetylation activity was 4.50 U mg–1. Based on the structural and molecular docking with 7-ACA, the catalytic active sites (Ser186-Asp354-His357) together with four substrate-binding residues (Asn259, Arg295, Thr355, and Leu356) of EstSJ are revealed. This study provided a promising 7-ACA deacetylase candidate that could be applied to produce D-7-ACA from 7-ACA in the pharmaceutical industry.